Industrial characteristics of wool produced from sheep fed on salt tolerant fodder crops - Helal A. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The present trial was conducted over 14 weeks and used twenty four males Barki lambs (18.8 Kg average body weight and 6 months of age) to investigate the effect of feeding salt tolerant plants on the industrial characteristics of raw and yarns of wool. Animals were fed on different salt tolerant plant mixture (47% Kochia and 53% Pearl millet grass) as hay (G2) or haylage with 5% molasses (G3), or Berseem hay as a control diet (G1). Haylage group had significant differences in fiber diameter, staple strength, staple elongation and medullated fibers compared with the hay group. The prickle factor found to be 49.2 (G1), 37.2 (G2) and 46.6 (G3) with significant differences (P<0.05) between both (G1) and (G3) compared with (G2). Staple strength found to be higher (P<0.05) in G1 (35.9 N/ktex) and G3 (35.7 N/ktex) compared with G2 (29.1 N/ktex). Yarn strength increased significantly (P<0.05) in the haylage group (7.2 kg) compared with the hay group (5.8 kg). Yarn irregularity represented by the number of thin and thick places as well as number of nodes, was significantly different (P<0.05) in both G2 and G3 compared with G1. It was concluded that haylage group had better wool characteristics than the hay group, while both treatments had lower wool characteristics compared to the control group. Correlations among both yarn and raw wool characteristics were also discussed.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)